The Variation of Fuel Mixture of Pertalite and Corncob Bioethanol on Engine Performance - Yuniarto Agus Winoko; Zulfikar Jabbaruddin Al Jihad Zulfikar; Umi Anis Ro'isatin (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
Year by year, fossil fuels start to run out due to the increasing marketing of fuel due to the increasing number of vehicles in Indonesia. It is proven by the increase in fuel prices in Indonesia, which means that the available oil is running low. To overcome the excessive use of fossil waste, researchers use alternative materials which are recycled from waste or commonly called bioethanol. The purpose of making a fuel mixture is that in addition to materials that are easily available, bioethanol does not damage the surrounding environment because it uses materials that do not contain harmful substances, which can be recycled such as fruit peels or plant waste. The study method used is experimental, using a Yamaha Force 115cc motorcycle. Data is obtained directly by observing the analysis of experimental results and then concluding in the form of graphs and tables. This test uses a dynamometer to determine the power and torque produced, while for testing the rate of fuel consumption using a measuring burette, then the calculation of fuel consumption is carried out. The results showed that there were differences in power, torque, Bmep and fuel consumption produced by variations in fuel. For maximum power produced on E15 fuel of 6.47 hp and a maximum torque of 5.16 Nm. For the lowest power produced on E20 fuel of 5.67 hp and the lowest torque of 4.39 Nm. The lowest fuel consumption was found in the use of E10 fuel of 0.000338 kg/hP while the highest fuel consumption was produced by E20 fuel of 0.0000406 kg/hP. For the highest Bmep on E15 fuel of 11.91 Psi and the lowest on E20 fuel of 11.39 Psi.